Dispelling the manufacturing myth : American factories can compete in the global marketplace - National Research Council (U.S.). Committee on Comparative Cost Factors and Structures in Global Manufacturing (Washington, D.C. : National Academy Press, 1992)
An examination of manufacturing costs in domestic and offshore factories to provide insight into the factory location and decision making process.
Executive summary -- Introduction -- Consumer electronics -- Semiconductors -- Automobiles -- Conclusion.
Print version record.
Includes bibliographical references (pages 101-103) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Manufacturing industries -- United States; Competition, International; Concurrence internationale; BUSINESS & ECONOMICS -- Industries -- General; Competition, International; Manufacturing industries; United States; Verarbeitende Industrie; Internationale Wettbewerbsfähigkeit; USA; plant location; -- factory site selection; -- global competition